2019
DOI: 10.1021/acssuschemeng.9b03436
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Simple Amides in the Selective Recovery of Gold from Secondary Sources by Solvent Extraction

Abstract: The recycling of metals from end-of-life secondary sources such as electronic waste remains a significant environmental and technological challenge currently detrimental to the development of circular economies. The complex nature of electronic waste, containing a myriad of different elemental metals, means that sophisticated yet simple separation methods need to be developed in order to recycle these valuable and often critical metal resources. In this work simple 2 primary, secondary, and tertiary amides are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 61 publications
3
35
0
Order By: Relevance
“…(Figure 4), which results in a L:Ta ratio of approximately 2 (slope of 1.71 ± 0.13), suggesting the formation of an ion pair such as [HL 2 ][TaCl 6 ] in the organic phase. This type of behaviour is similar to that seen previously for Au extraction using L in which experimental and computational analysis showed that two amides chelate a proton through the oxygen atoms to form a charge-diffuse cation that can interact with diffusely charged metalate anions through classical (N-H•••X) and non-classical (C-H•••X) hydrogen bonds [23,24]. Direct structural characterisation of the extracted species has so far proven inconclusive, although 1 H NMR studies provide an indication as to how the receptor [HL2] + is interacting with the metalate ( Figure 5).…”
Section: Structure Elucidationsupporting
confidence: 86%
See 3 more Smart Citations
“…(Figure 4), which results in a L:Ta ratio of approximately 2 (slope of 1.71 ± 0.13), suggesting the formation of an ion pair such as [HL 2 ][TaCl 6 ] in the organic phase. This type of behaviour is similar to that seen previously for Au extraction using L in which experimental and computational analysis showed that two amides chelate a proton through the oxygen atoms to form a charge-diffuse cation that can interact with diffusely charged metalate anions through classical (N-H•••X) and non-classical (C-H•••X) hydrogen bonds [23,24]. Direct structural characterisation of the extracted species has so far proven inconclusive, although 1 H NMR studies provide an indication as to how the receptor [HL2] + is interacting with the metalate ( Figure 5).…”
Section: Structure Elucidationsupporting
confidence: 86%
“…The simple primary amide, L, shows excellent performance for tantalum recovery by solvent extraction under high chloride conditions. The extraction mechanism is identified as similar to that seen for the recovery of gold by L, in which charge-diffuse protonated receptors are formed that preferentially interact with the charge diffuse monoanionic metalate [AuCl 4 ] − [23,24]. 1 H and 13 C NMR data are consistent with a strong outer-sphere interaction between [HL 2 ] + and [TaCl 6 ] − .…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…Among these residues, the materials generated from the electronic and communication industries are of importance [1,2], because they contained, among other valuable metals, gold. Thus, there is an interest, from worldwide researchers, to investigate methods for the recovery of this precious metal from these residues or, in general, gold-bearing wastes [3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%